2021
DOI: 10.1155/2021/5518195
|View full text |Cite
|
Sign up to set email alerts
|

Association between Periodontal Disease and Comorbidities in Saudi’s Eastern Province

Abstract: The incidence of periodontal diseases is associated with multiple comorbidities that influence a patient’s treatment planning. This study evaluates the relation between periodontal disease and multiple comorbidities reported in the Saudi population from the Eastern province. This study was conducted on 190 patients, who visited the periodontology clinics at Imam Abdulrahman Bin Faisal University, Saudi Arabia. Demographic data, smoking habits, past medical and dental histories, blood pressure, random blood glu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 45 publications
2
6
1
Order By: Relevance
“…Moreover, there was a significant positive correlation between the number of missing teeth and the presence of systemic disease (p = 0.001). In line with the present results, Madi, et al [24] also reported that the risk of both alveolar bone and tooth loss was statistically higher in periodontitis patients with systemic diseases including HT and diabetes. On the other hand, Sperr, et al [25] reported that periodontitis severity was not significantly associated with systemic diseases.…”
Section: Resultssupporting
confidence: 92%
“…Moreover, there was a significant positive correlation between the number of missing teeth and the presence of systemic disease (p = 0.001). In line with the present results, Madi, et al [24] also reported that the risk of both alveolar bone and tooth loss was statistically higher in periodontitis patients with systemic diseases including HT and diabetes. On the other hand, Sperr, et al [25] reported that periodontitis severity was not significantly associated with systemic diseases.…”
Section: Resultssupporting
confidence: 92%
“…5,6,10,[18][19][20] In line with the current research, periodontitis is found extensively in the middle-aged, namely in the 40 to 59 age group, after which the incidence decreases. 1 The results of the present study show that rate of periodontitis decreases at the age of 60 years and over. 10,20,21 This phenomenon indicates that the age group experienced a higher rate of tooth loss due to periodontitis.…”
Section: Discussionsupporting
confidence: 52%
“…6 Periodontitis is a chronic multifactorial inflammatory disease identical to immune dysfunction that was previously induced by bacterial infection, mainly anaerobic gram-negative bacteria, which causes progressive damage to the soft and hard tissues supporting the teeth. 1,[7][8][9][10][11][12][13] Periodontal bacterial infection increases systemic inflammatory markers, which also initiates various systemic diseases, including stroke. 8,14,15 Stroke is considered the most common cause of death due to periodontal disease and is currently a massive epidemic in numerous developed and developing countries.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Periodontal disease is a serious issue in Taiwan; the prevalence of periodontitis has significantly increased in Taiwan over the past years [ 5 ]. There are multiple comorbidities, such as pulmonary, endocrinal, metabolic, cardiovascular, neurological, hematological, and skeletal disorders, associated with periodontal disease [ 6 , 7 , 8 ]. For example, the increased risk of periodontitis in patients with diabetes is estimated to be 2–3 fold; that is, it increases the risk for periodontitis 2–3 times [ 9 ].…”
Section: Introductionmentioning
confidence: 99%